A Comparison of the Application of Artificial Intelligence in the Educational System - Rabeya, Mosa; Mahmud, Md. Shihab; Johora, Sayada Fatima Tuj; Sattar, Abdus (2022 International Conference on Emerging Trends in Computing and Engineering Applications (ETCEA), 2022)
Artificial intelligence (AI) has made considerable strides in educational technologies in recent decades. The goal of this study was to analyze and explain Artificial Intelligence in Education (AIED). AI, a concept coined in the distant past to refer to the method of imputing human intelligence to machines, has made great strides in the quickly advancing modern society. Thus, the idea of fusing education and artificial intelligence emerged, ushering in the twenty-first century. The recent study, however, shows that instructional techniques are benefiting from artificial intelligence studies. This article gives a broad overview of various implementation methods for AI-based technologies in the education industry. These tools have made education easier and more interesting for both professors and students. We now have an educational environment that is already set up thanks to AI, complete with a range of specialist system applications, collaborative robots, intelligent AI assistants, and a smart learning environment. Additionally, this paper mentions a number of models that have been proposed for this subject and has good possibilities going forward. As a result, we shall draw the conclusion from this review study that artificial intelligence appears to have a bright future in the field of education.